2019
DOI: 10.1249/mss.0000000000001846
|View full text |Cite|
|
Sign up to set email alerts
|

Grounded Running Reduces Musculoskeletal Loading

Abstract: Purpose Recent observations demonstrate that a sizeable proportion of the recreational running population runs at rather slow speeds and does not always show a clear flight phase. This study determined the key biomechanical and physiological characteristics of this running pattern, i.e., grounded running (GR), and compared these characteristics with slow aerial running (SAR) and reference data on walking at the same slow running speed. Methods Thirty ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 24 publications
1
45
0
Order By: Relevance
“…However, it has been shown that quadrupeds, such as elephants, run without a t f [3]. Similarly, several bipeds use an intermediate gait, termed grounded running by Andrada et al [4], that shares the characteristics of the spring–mass model of running during stance, but is deprived of a t f [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been shown that quadrupeds, such as elephants, run without a t f [3]. Similarly, several bipeds use an intermediate gait, termed grounded running by Andrada et al [4], that shares the characteristics of the spring–mass model of running during stance, but is deprived of a t f [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a study [5] observed modifications of biomechanical and metabolic parameters in runners that performed instructed grounded running at a slow speed (2.1 m·s −1 ). When using this intermediate form of gait instead of their natural running gait, runners decreased their musculoskeletal load but increased their energy expenditure [5]. In this particular style of gait, the presence of a t f does not appropriately discriminate walking and running.…”
Section: Introductionmentioning
confidence: 99%
“…Grounded running incurs a lower vertical, but larger antero-posterior oscillation of the COM with each stride. 12 With a reduced vertical oscillation of the COM, -Duty Factor 12-14 22 ↑ Leg Stiffness 14 ↓ vGRF 11 12 14 ↓ ✗, Absent; ✓, Present; ↓, Lower; ↑, Higher; -, No difference; COM, Centre of mass; vGRF, Vertical ground reaction force.…”
Section: Biomechanics Of Grounded Runningmentioning
confidence: 99%
“…12 However, when grounded running was compared to aerial running at a population average speed (3.2 m•s −1 ), an approximate 25% increase in energy expenditure was observed compared to aerial running. 12 The elevated metabolic cost is likely a primary explanation for why many humans do not naturally use a grounded running technique. This notion is supported by Iwami and Ogihara's 14 finding that grounded running was difficult to adopt as it was more exhaustive.…”
Section: Energetics Of Grounded Runningmentioning
confidence: 99%
See 1 more Smart Citation